Value of Social Care Character Through Education and Community Activities - Muhammad Fauzi Fitri Andika (Yayasan Keluarga Guru Mandiri, 2022)
This research aims to describe the value of social care character through community activities. This research is a qualitative study that uses descriptive methods of analysis that take the setting of the community in Demangan Village, Karangdowo Kebupaten Klaten District.Â The subject of his research is the community in Demangan Village. Data collection uses observation, interview, and documentation techniques. The results showed that the research method of planting social care character in the community environment of Demangan Village, Karangdowo District, Klaten Regency, namely through exemplary and habituation carried out daily.Â The example of the value of social care through teaching from the family in Demangan Village itself. While the habituation of social care character through activities carried out in the community such as gotong royong, building places of worship and houses of citizens, cleaning roads, marriage, and other events that are around the world.